A Students’ Psychological Factor that Causes Difficulty in Learning Speaking English - Mahmudin, Usman (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2023)
This research is qualitative research that was conducted on July 18, 2023, at State Vocational High School 10 Bandung (SMKN 10 Bandung). This research aims to analyze the psychological factors that are mostly faced by 11th-grade students of Karawitan of SMKN 10 Bandung and to find out their responses to their difficulties. The participants in this research consisted of 35 students, one class, grade 11 of Karawitan. In this research, the researcher used a qualitative approach with a case study design. In collecting the data, the researcher used some instruments such as observation, field notes, questionnaires, and interviews. To collect the data, the researcher used an observation checklist, field notes, questionnaires, and interviews with the participants to find out the psychological factors mostly faced by the students in speaking English. There were 35 students of Karawitan as participants in this research. All students are well observed and they are required to fill in the questionnaires about psychological factors that cause difficulty in speaking English which were introduced by Juhana. Meanwhile, the interview consisted of 17 questions arranged to find out how they respond and deal with their difficulties. Researchers used data analysis to identify the psychological factors faced by students. The results of this study indicate that the psychological difficulties that faced by students when speaking English are related to grammar, pronunciation, vocabulary, anxiety, and shyness. In conclusion, the difficulties faced by students of State Vocational High School 10 Bandung are caused by psychological factors such as motivation, lack of confidence, afraid of making mistakes, etc.